Work process of managers of Primary Health Care managers during the covid-19 pandemic (Revista Contexto & Saúde, 2025)
Objective: To understand the work process of Primary Health Care (PHC) managers during the COVID-19 pandemic. Method: A qualitative, descriptive-exploratory study with data collected through semi-structured interviews with 11 managers. Thematic content analysis was carried out based on the theoretical framework of the health work process and the psychodynamics of work. Results: Five thematic categories were constructed: 1. Production in action: reformulations of the service to maintain PHC as the gateway to the SUS, in which the managers pointed out the reformulation of the service to keep care in PHC; 2. New flows to serve users in the context of the pandemic in the healthcare network; 3. Democratization of management: participatory versus autocratic in planning and decision-making; 4. Precarious working conditions and the sickening of frontline workers; 5. Weaknesses imposed by the pandemic: mischaracterization of comprehensive and longitudinal care in PHC. Conclusion: The research made it possible to produce memories and learnings to understand the crossings in the work process of managers, between prescribed and actual work, and the objective and subjective aspects of this complex web of initiatives.
Keywords: Primary Health Care; COVID-19; Health Management; Unified Health System; Work